Reverse-phase liquid chromatography with electrospray ionization/mass spectrometry for the quantification of pseudoephedrine in human plasma and application to a bioequivalence study - Kim, Jin-Ki; Jee, Jun-Pil; Park, Jeong-Sook; Kim, Hyung Tae; Kim, Chong-Kook (Arzneimittelforschung, 2011)
A sensitive and selective reverse-phase liquid chromatography electrospray ionization mass spectrometry (LC-ESI-MS) method was developed and validated to quantify pseudoephedrine (CAS 90-82-4) in human plasma. Phenacetin was used as the internal standard (I.S.). Sample preparation was performed with a deproteinization step using acetonitrile. Pseudoephedrine and I.S. were successfully separated using gradient elution with 0.5% trifluoroacetic acid (TFA) in water and 0.5% TFA in methanol at a flow-rate of 0.2 mL/min. Detection was performed on a single quadrupole mass spectrometer by a selected ion monitoring (SIM) mode via electrospray ionization (ESI) source. The ESI source was set at positive ionization mode. The ion signals of m/z 166.3 and 180.2 were measured for the protonated molecular ions of pseudoephedrine and I.S., respectively. The lower limit of quantification (LLOQ) of pseudoephedrine in human plasma was 10 ng/mL and good linearity was observed in the range of concentrations 10–500 ng/mL (R2 = 1). The intra-day accuracy of the drug containing plasma samples was more than 97.60% with a precision of 3.99–11.82%. The inter-day accuracy was 99.36% or more, with a precision of 7.65–18.42%.By using this analytical method, the bioequivalence study of the pseudoephedrine preparation was performed and evaluated by statistical analysis of the log transformed mean ratios of pharmacokinetic parameters. All the results fulfilled the standard criteria of bioequivalence, being within the 80–125% range which is required by the Korea FDA, US FDA, and EMEA to conclude bioequivalence. Consequently, the developed reverse-phase LC-ESI-MS method was successfully applied to bioequivalence studies of pseudoephedrine in healthy male volunteers.
Keywords: Bioequivalence; CAS 90-82-4; Human plasma; LC-ESI-MS; Pharmacokinetics; Pseudoephedrine